Effectiveness Of Antipyretic Leaf Extracts Of Frown (Ipomoea Pescaprae L.) In Rats - Fahma Shufyani; Ani Rahmadhani Kaban; Saiyidatul Fadhilah Pane (Pena Cendekia Insani, 2022)
Fever is a condition where the body temperature is above normal (Wardiyah et al., 2016). Normal human body temperature ranges from 36-37°C, fever can exceed 37°C (Kurniati, 2016). The purpose of this study was to determine the fever-reducing effect of Katang-Katang leaf extract (Ipomoea pescaprae L.) on rats induced with baker's yeast. The method used in this research is experimental laboratory. The test animals used were 25 rats which were divided into 5 treatment groups, each group consisted of 5 rats. The positive control group used paracetamol 500 mg/kgBW, the negative control group used 1% CMC Na and the EEDK treatment group with doses of 100, 200, 300 mg/kgBW given orally. Mice were induced with 0.2 ml baker's yeast subcutaneously (s.c). Measurements of the rectal temperature of rats were carried out before and after yeast administration after treatment in consecutive tests at 4, 8, 12, 16 and 20 minutes. with EEDK at doses of 200 and 100 mg/kgBW, while paracetamol gave a greater decrease in rectal body temperature in rats than at a dose of 300 mg/kgBW. The results of the analysis showed that EDK doses of 100, 200, and 300 mg/kgBW did not have a significant difference with paracetamol at a dose of 65 mg/kgBW (P>0.05). It can be concluded that EEDK has the same effect as reducing fever in rats but not better than paracetamol. Suggestions for further researchers to carry out this research into dosage form and measure its toxicity.